Implantação de sistema de energia eólica de pequena escala em uma escola particular na cidade de Currais Novos/RN - Medeiros, Erhos Sanders Macêdo (Universidade Federal Rural do Semi-Árido, 2020)
Given the scenario in which we are inserted, where natural resources are increasingly scarce, the search for alternatives that aim to reduce environmental degradation and emission of polluting gases has become something more common and researched. World powers have been concerned with showing the world that it is possible to have energy in a less impactful way. Therefore, the use of renewable energies has become a reality in our daily lives. For years, wind farms have been installed ever closer to civilizations, since they do not have a high impact on the population living in the surroundings. However, small systems have recently started to be implemented in private homes and institutions, integrated into the electricity grid, generating consumer credits, which are directly deducted from the energy bill. Thus, this work aims to carry out a case study in a private educational institution in the city of Currais Novos / RN, which seeking to save money on its energy bill, installed small wind towers on its premises. However, due to problems related to the installation project, the system did not meet the owner's expectations. A questionnaire was developed to answer questions related to the project, and with the help of it, it was possible to develop an analysis of the possible problems of the system in operation.
Monografia
Keywords: Fontes renováveis; Energia eólica; Sistemas eólicos de pequeno porte; Renewable sources; Wind energy; Small wind systems; ENGENHARIAS::ENGENHARIA CIVIL